Use of WhatsApp to enhance grammar and vocabulary in university english foreign learners - Contreras Jordán, Rosa Marianella; Almache Granda, Gabriela Katherine; Sandoval, María José (Journal of Science and Research, 2021)
The purpose of this study is to examine the results of mobile instruction by WhatsApp application in 30 students (experimental group). Participants were EFL (English Foreign Learners) students at the University Technical of Babahoyo located in Los Ríos - Ecuador. This action research study used quantitative data gotten from pre-tests and post-tests. Evidence showed that students improved 37.12% on their vocabulary and 37.55% on their grammar competence. It was corroborated by the p-value 000 < 0,05. Moreover, the effect size according to Cohen´s was large with 2.5 in the post-tests´ comparison between the control and experimental groups. Also, a comparison between pre-tests in the control and experimental groups assured that samples had similar English level proficiency. Finally, the teacher´s observations stated that students´ attitudes toward WhatsApp mobile instruction and flipped approach were positive.